Mengoptimalkan Komunikasi Orang Tua dan Anak Usia Dini - Mhd Zulfan Nur; Dini Pransiska; Naila Pajira; Nurbety Sijabat; Aman Simare-mare; Elya Siska Anggraini (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research discusses effective communication between parents and early childhood as a key aspect of a person's development. Effective communication can create understanding, happiness, positive influence on attitudes, and harmonious relationships. This study uses qualitative descriptive methods to observe and describe communication phenomena in natural conditions. Data collection techniques include direct observation, in-depth interviews with parents, and analysis of supporting documents. Researchers hope that these findings will add insight regarding the importance of good parental communication as a basis for personality formation and child development. By understanding the role of communication, it is hoped that a family environment can be created that supports children's growth into emotionally and socially healthy individuals